Acceptance and commitment therapy’s effectiveness in reducing depression in women leaving crystal - Fatemeh Golshani, Maryam Mohammadi, Fariba Hassani, Suzan Emamipour, (Opción, 2019)
The aim of this research was to study the effectiveness of acceptance and commitment therapy in decreasing depression of women leaving crystal. Our research method was quasi-experimental of the kind of pre-test-post-test with the control group. The findings showed that acceptance and commitment therapy for reducing depression in women who have been leaving crystal is effective and there is a significant difference between the scores of experiment and control groups of depressed women leaving crystal and the acceptance and commitment therapy shows therapeutic effects in the field of reducing depression of women consuming crystal.